Application of HEC-RAS Software for Sediment Transport Analysis in Sg. Muda River - Mohd Shukri, Batrisyia Huda; Abu Talib, Siti Hidayah (Recent Trends in Civil Engineering and Built Environment, 2024)
Sedimentation is the accumulation of sediment on the land surface or the bed of a watercourse. Sedimentation in rivers leads to the raising of bed level resulting in flash flood during heavy rainfall. Muda has suffered extensive environmental degradation, mostly as a result of significant erosion and sedimentation due to the effect of rapid urbanization. Excessive sediments can harm the ecological health of waterways and reduce their ecological, social and cultural values. Large accumulations of sediment can cause further erosion by causing upstream flooding or diverting the flow to adjacent river banks or even adjacent land. This study is carried out to simulate analysis of the sediment transport rates at Sg. Muda, Kedah river area by using one-dimensional (1D) quasi unsteady flow HEC-RAS. Some information such as hydrological data, geometric data and sediment data are needed to run the HEC-RAS simulation. The analysis is done by using Laursen-Copeland method as it performs in the very fine sand and very coarse silt range. The result shows the location of erosion and deposition occurs. The changes in longitudinal profiles, velocity and shear stress variation along the river, mass inflow and outflow, bed level change of river and sedimentation concentration are the output from HEC-RAS model analysis. The maximum depth of erosion in these reaches is about - 3020 m which happens in STN 5027 river reach stations and the maximum deposition is about 9513 m in downstream STN 20772 reach of river having wide cross section. The maximum sediment concentration along Sg. Muda is obtained to be 11861 mg/L. The main advantage of this study is that it will help in achieving successful strategies for reducing sediment can be used for a long time.